Regulatory Aspects of Gene Therapy and Cell Therapy Products A Global Perspective - Galli, Maria Cristina.; Galli, Maria Cristina.; Serabian, Mercedes.; Serabian, Mercedes. (American Society of Gene & Cell Therapy, 2015)
Medical literature for health care practitioners on the evaluation and treatment of breastfeeding issues has been disjointed, conflicting, and difficult to find. The field of breastfeeding medicine itself is nonexistent—there are no "breastfeeding doctors" who are specifically trained to understand this complex and interactive process. While much of the literature about breastfeeding describes how it "should" work, there is currently nothing available to explain why it often fails and how to treat it. Clinician’s Guide to Breastfeeding: Evidence-based Evaluation and Management is written for health care practitioners who work with breastfeeding mothers; physicians, nurses, nurse practitioners, and lactation consultants. It provides clear information and clinically tested strategies to help professionals guide new mothers to breastfeed successfully. The first of its kind to consider the entirety of the breastfeeding experience, Clinician’s Guide to Breastfeeding is written by Dr. Linda D. Dahl, a leading expert on the subject. It is a comprehensive review of breastfeeding, covering objective analyses of ideal or “normal” nursing, as well as the evaluation and treatment of abnormal nursing, including case studies to illustrate the treatment decision-making process.